Prevalence of human papillomavirus genotype among Moroccan women during a local screening program - Zaitouna Alhamany; Mohammed El Mzibri; Aicha Kharbach; Abderrahman Malihy; Redouane Abouqal; Hassan Jaddi; Ali Benomar; Mohammed Attaleb; Najat Lamalmi; Nadia Cherradi (Journal of Infection in Developing Countries)
Introduction: Many studies have indicated a causal relationship between genital human papillomavirus (HPV) infections and cervical cancer. This study aimed to determine the prevalence and genotypes of six high-risk oncogenic human papillomaviruses in cervical lesions from Moroccan women with normal and abnormal cytology.